Lost in Translation: The Politics of Indonesian Literature in International Literary Spaces - Angelianawati, Desca; Leba, Seli Marlina Radja; Fachrul, Rukmana; Indriyanto, Kristiawan (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study examines the cultural politics affecting Indonesian literature in the global literary arena. It analyses how literary politics, standardisation, implicit agendas, and validation systems impact international reception. The study investigates how global literary standards reshape Indonesian narratives to match international preferences, often at the expense of cultural authenticity. In addition, several works by some prominent Indonesian authors, including Toer, Anwar and Kurniawan are being analysed. Using a descriptive-qualitative approach with discourse analysis, interview and case studies, the research reveals three key findings: translation challenges for Indonesian literary works, limited international publication opportunities, and underrepresentation in global literary awards and criticism. Based on these findings, the study advocates for more inclusive literary practices to enhance Indonesian literature’s global visibility while preserving its cultural integrity.